O efeito do anúncio das Fusões e Aquisições ao nível das rendibilidades anormais - Oliveira, J.; Vieira, Elisabete; Lobo, Bruno (2023 18th Iberian Conference on Information Systems and Technologies (CISTI), 2023)
Mergers and acquisitions (M&A) are very complex restructuring operations that have dominated in recent years. The announcement of an F&A operation is seen as a sign that companies give to the market, and it can generate abnormal positive or negative returns on shareholder return. The present study aims to analyze the evolution of scientific production on the effect of the announcement of F&A operations at the level of abnormal returns. This review was elaborated using formal methods of bibliometric analysis and the process of collection and selection of articles was carried out in the Scopus database. The final selection had 205 documents from 2012 to 2022, aiming to analyze the recent literature on this topic. The results suggest that the total number of publications on this topic has been increasing, reaching in 2022, the maximum number of articles published. Regarding the most relevant authors, there is not only one highlight, since four authors present a total of four published articles. The most relevant journal is the Journal of Corporate Finance, where fifteen articles were published in a total of 205 and the most cited by the documents analyzed was the Journal of Financial Economics. The countries that have the most published articles on this topic are the USA, the UK, Australia, China and India. However, the continents that are most investigated are the American and Asian continent, and there is a lack of recent studies investigating the European continent and there is also no evidence of research relating the markets of different continents. The relevant topics that can be explored in future investigations are mergers and acquisitions, cumulative abnormal return (CAR) and mergers & acquisitions performance.